Cross-cultural encounters on the Ukrainian steppe : settling the Molochna basin, 1783-1861 - Staples, John Roy, 1961- (Tsarist and Soviet Mennonite studies., 2003)
In a regional history of colonization and adaptation in southern Ukraine, Staples examines how diverse agrarian groups, faced with common environmental, economic, and administrative conditions, followed sharply divergent paths of development.